How Do Banks Interact with Fintechs? Forms of Alliances and their Impact on Bank Value - Lars Hornuf; Milan F. Klus; Todor S. Lohwasser; Armin Schwienbacher (Center for Economic Studies and ifo Institute (CESifo), 2018)
The increasing pervasiveness of technology-driven firms that offer banking services has led to a growing pressure on traditional banks to modernize their core business activities. Banks attempt to confront the challenges of digitalization by cooperating with financial technology firms (fintechs) in various forms. In this paper, we investigate the factors that drive banks to form alliances with fintechs. Furthermore, we analyze whether such bank-fintech alliances affect the market valuation of banks. We provide descriptive evidence on the different forms of alliances occurring in practice. Using hand-collected data covering the largest banks from Canada, France, Germany, and the United Kingdom, we show that banks are significantly more likely to form alliances with fintechs when they pursue a well-defined digital strategy and/or employ a Chief Digital Officer. We evidence that markets react more strongly if digital banks rather than traditional banks announce a bank-fintech alliance. Finally, we find that alliances are most often characterized by a product-related collaboration between the bank and the fintech and that banks most often cooperate with fintechs providing payment services.
Keywords: G21; G23; G34; M13; 330; fintech; strategic alliance; entrepreneurial finance; financial institutions; banks